PENGARUH RISIKO KEUANGAN, MANAJEMEN LABA DAN PERTUMBUHAN PENJUALAN TERHADAP NILAI PERUSAHAAN DENGAN ROE DAN DER SEBAGAI VARIABEL KONTROL PADA PERUSAHAAN SEKTOR PROPERTI, REAL ESTATE DAN BUILDING CONTRUCTION - Yamasitha Yamasitha (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2020)
The objective of this research is to analyze the effect of financial risk, earning management and sales growth on firm value. Financial risk (DAR), earning management (EM), and sales growth (PP) are used as independent variable and firm value (PBV) are used as dependent variable. Two variables are used as control variables is ROE and DER. The type of data is secondary data from the financial statements and annual report for 2013 to 2017. The population of this research is property, real estae and building contruction sector componies listed in Indonesia Stock Exchange. Methods of analysis is used a classic assumption test and panel data regression analysis. The result of the regression analysis in this research showed fiancial risk, earning management and sales growth has no effect significant on firm value. ROE and DER has a significant effect on firm value. And jointly fiancial risk, earning management, sales growth, ROE and DER has a significant effect on firm value. The discussion and research that will come under discussion on this research.